Perlindungan Hukum terhadap Hak Kesehatan Anak dari Bahaya Jajanan Sekolah di Kota Kupang - Viadora Asnawi; Yohanes G. Tuba Helan; Detji K. E. R. Nuban (Jurnal Hukum dan Sosial Politik, 2024)
The purpose of this research is to analyze the legal protection of children's health rights from the dangers of school snacks in Kupang City. This research is an empirical research, which uses data collection techniques through interviews, documentation studies to obtain primary and secondary data on Legal Protection of Children's Health Rights from the Dangers of School Snacks in Kupang City, with 11 respondents, data analyzed descriptively qualitative. The results showed that the legal protection of school children as consumers of PJAS (School Snack Food) in Kupang City, in conducting legal protection of school children has not been effective because BPOM conducts surveillance in schools in Kupang city only taking sampling from several schools in Kupang city. The efforts of POM Center in Kupang in supervising PJAS (school snacks) in Kupang City, in performing the supervisory function of safe PJAS in Kupang City are limited experts to conduct supervision in the field, the rise of online sales, the low level of public education and the lack of strict law enforcement. (3) Are the prevention efforts carried out by the POM Center in Kupang against PJAS (school snack food) traders in Kupang City, the Food and Drug Supervisory Agency has not been maximized in sanctioning school snack food traders who are proven to use hazardous ingredients in processed food.